Sigma Coordinate Pressure Gradient Errors and the Seamount Problem - Mellor, G. L.; Oey, L-Y.; Ezer, T. (Journal of atmospheric and oceanic technology, 1998)
In a recent paper by Mellor et al., it was found that, in two-dimensional (x, z) applications with finite horizontal viscosity and zero diffusivity, the velocity error, associated with the evaluation of horizontal density or pressure gradients on a sigma coordinate grid, prognostically disappeared, leaving behind a small and physically insignificant distortion in the density field. The initial error is numerically consistent in that it decreases as the square of the grid increment size.